Implementation of Technology-Based Learning in Social Sciences Learning - Unsah Unsah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study examines the implementation of technology-based learning in Social Studies (IPS) for students at MTs Al Khairiyah Koja in secondary schools. The purpose of this study was to determine how technology is applied in the Social Studies (IPS) learning process for students at MTs Al Khairiyah Koja and its impact on student interest and learning outcomes. The research method used was a qualitative, descriptive approach through classroom observations, interviews with teachers and students, and analysis of learning documents. The results showed that the use of technology such as computers, learning applications, and digital resources significantly increased learning activities, student engagement, and understanding of Social Studies (IPS) concepts among students at MTs Al Khairiyah Koja. Despite several obstacles such as limited equipment and teacher skills, overall, technology made a positive contribution to Social Studies (IPS) learning at MTs Al Khairiyah Koja.